Identifying Priority Areas for Coastal Protection Around Java, Indonesia - Jimy Kalther; Akemi Itaya (Politeknik Kelautan dan Perikanan Dumai, 2021)
Climate change-induced sea level rise will likely increase the severity of ongoing coastal disasters in Indonesia. The selection and concentration approach should be applied to minimize the costs of conservation when budgets are limited. Prioritizing is then effective in terms of cost effectiveness. We aimed to identify priority areas for coastal protection against sea level rise around Java, Indonesia, using the Marxan model. The model uses systematic planning to select prioritized areas for coastal protection. Three scenarios were developed based on ecological, economic, and disaster elements that were exacerbated by sea level rise. A scenario is defined as a particular simulation circumstance based on assumptions about extrinsic drivers, parameters, and the structure of the model. Coastline length, mangrove coverage, low-elevation area, fishpond area, human settlement area, and the area of zones with the potential for annual rainfall increases acquired from DIVA-GIS and WorldClim were set as environmental factors. There were 60 areas facing the coast among 117 areas. For those protection, it would be fairly costly. We were able to narrow that number down from 18.8% to 62.4% from 117 areas using our method. This might become very cost effective. The most prioritized areas were located in the northern region of Java. These areas can be a focus of preferential effort and funding for conservation. The results of this study will help to make the protection strategy based on not only the magnitude of damage but also the total perspective using public data that is relatively easy to obtain.